Pupillometry-guided Intraoperative Remifentanil Administration versus Standard Practice Influences Opioid Use: A Randomized Study. (August 2017) - Sabourdin, Nada; Barrois, Jérôme; Louvet, Nicolas; Rigouzzo, Agnès; Guye, Marie-Laurence; Dadure, Christophe; Constant, Isabelle
Abstract : Background: Pupillometry has shown promising results for assessing nociception in anesthetized patients. However, its benefits in clinical practice are not demonstrated. The aim of this prospective randomized study was to evaluate the impact of intraoperative pupillometry monitoring on perioperative opioid consumption in major gynecologic surgery. Methods: After receiving ethics committee approval and written consent of patients, American Society of Anesthesiologists status I to II women undergoing gynecologic surgery were included in this single-blinded, prospective, parallel-arm randomized study. General anesthesia was standardized with propofol–remifentanil target-controlled infusion. Patients were randomly assigned into two groups. In the pupillometry group, remifentanil administration was guided by pupillary diameter changes. In the standard group, remifentanil administration was left to the discretion of the anesthesiologist. The primary outcome was intraoperative remifentanil consumption. Results: Fifty-five patients were analyzed. Remifentanil consumption was markedly decreased in the pupillometry group (3.8 [3.4 to 4.8 µg · kg –1 · h –1 ] vs. 7.9 µg · kg –1 · h –1 [6.5 to 9.0 µg · kg –1 · h –1 ] in the standard group; difference = 4.2 µg · kg –1 · h –1 [95% CI, 3.0 to 5.3 µg · kg –1 · h –1 ]; P < 0.001). Cumulative 0- to 12-h morphine consumption was reduced in the pupillometry group (two-way repeated measures ANOVA 0.3 ± 0.1 vs. 0.4 ± 0.2 mg/kg; P = 0.048). A telephone survey 3 months after surgery revealed that 15 of 29 patients in the standard group still experienced procedure-related pain versus 3 of 23 in the pupillometry group (chi-square P = 0.037). No adverse events associated with pupillometry were observed during the study. Conclusions: The use of pupillometry to guide intraoperative analgesia reduced intraoperative remifentanil consumption and postoperative morphine requirements. The possible consequences of decreasing intraoperative remifentanil in terms of chronic pain require further investigation. Abstract : Objective pupil measurements were used to guide intraoperative remifentanil dosing in order to maintain postinduction pupil diameter. In a randomized study, compared with standard approaches, patients in whom remifentanil dosing was pupillometry guided received 50% less intraoperative remifentanil and needed slightly less postoperative patient-controlled analgesia morphine.